Glucose-Impaired Corneal Re-Epithelialization Is Promoted by a Novel Derivate of Dimethyl Fumarate - Giovanni Giurdanella; Anna Longo; Loredana Salerno; Giuseppe Romeo; Sebastiano Intagliata; Gabriella Lupo; Alfio Distefano; Chiara Bianca Maria Platania; Claudio Bucolo; Giovanni Li Volti; Carmelina Daniela Anfuso; Valeria Pittalà (MDPI AG, 2021)
Glucose induces corneal epithelial dysfunctions characterized by delayed wound repair. Nuclear erythroid 2-related factor 2 (Nrf2) mediates cell protection mechanisms even through the Heme oxygenase-1 (HO-1) up-regulation. Here, we synthesized new HO-1 inducers by modifying dimethyl fumarate (DMF) and used docking studies to select VP13/126 as a promising compound with the best binding energy to Kelch-like ECH-associated protein 1 (keap1), which is the the regulator of Nrf2 nuclear translocation. We verified if VP13/126 protects SIRC cells from hyperglycemia compared to DMF. SIRC were cultured in normal (5 mM) or high glucose (25 mM, HG) in presence of DMF (1-25 μM) or VP13/126 (0.1-5 μM) with or without ERK1/2 inhibitor PD98059 (15 μM). VP13/126 was more effective than DMF in the prevention of HG-induced reduction of cell viability and proliferation. Reduction of wound closure induced by HG was similarly counteracted by 1 μM VP13/126 and 10 μM DMF. VP13/126 strongly increased phospho/total ERK1/2 and restored HO-1 protein in HG-treated SIRC; these effects are completely counteracted by PD98059. Moreover, high-content screening analysis showed a higher rate of Nrf2 nuclear translocation induced by VP13/126 than DMF in HG-stimulated SIRC. These data indicate that VP13/126 exerts remarkable pro-survival properties in HG-stimulated SIRC, promoting the Nrf2/HO-1 axis.